Vulvoscopía and directed biopsy in vulvar infection by human papillomavirus - Herrera, Gustavo (2015)
Human papillomavirus (HPV) vulvar infection is the most frequent pathology of external genitalia. Because the infection is often subclinical, the use of vulvoscopy and directed biopsy is needed for a correct diagnosis. During one year, 316 women were studied by colposcopy and biopsy. At least one vulvar pathology was diagnosted in 86 cases (27,22%); HPV (68,6%). Active sexual women were more affected. Nearly half of cases were subclinical and the diagnosis was perfomed by colposcopy and biopsy. The vulvar fork and the inner face of labia minora appear as frequent localizations. In 20% of cases, the HPV infection involved also cervix and vagina; different grades of cervical neoplasia were seen in 45% of infected patients. Oral contraceptives, IUD and bilateral salpingotomy appear to be risk factors to develop vulvar infection.